Negative association of C-reactive protein-albumin-lymphocyte index (CALLY index) with all-cause and cause-specific mortality in patients with cancer: results from NHANES 1999–2018 - Zhu, Di; Lin, Ye-Ding; Yao, Yan-Zhu; Qi, Xiang-Jun; Qian, Kai; Lin, Li-Zhu (BMC cancer, 2024)
The CALLY index, which is derived from C-reactive protein (CRP) content, serum albumin level, and total lymphocyte count, reflects the immune, nutritional, and inflammatory status of the body. Lack of sufficient evidence on the correlation between the CALLY index and the prognosis of cancer patients with various cancer forms. This study seeks to elucidate the association between the CALLY index and mortality from all causes as well as specific causes in cancer patients within a U.S. This investigation encompassed 3511 cancer-afflicted adults from the National Health and Nutritional Examination Surveys (NHANES) spanning 1999 to 2018. The CALLY index was measured at baseline only. The relationship between the CALLY index and mortality from both all causes and cancer specifically was examined using Cox proportional hazards models. Additionally, restricted cubic spline, piecewise linear regression, and various subgroup and sensitivity analyses were employed. Over a median follow-up of 103 months, 1,355 deaths occurred, and the incidence of all-cause mortality for these participants was 38.34%. Our findings indicate that an elevated CALLY index correlates with a diminished risk of all-cause mortality. Upon applying a natural logarithmic transformation to the CALLY index, the comprehensively adjusted model revealed that each one-unit increment in ln CALLY corresponded to a 18% decrease in all-cause mortality risk among cancer patients (HR = 0.82, 95% CI:0.79-0.86). Analyses of mortality due to cardiac and cancer-related causes yielded consistent results, which were robust across various subgroup and sensitivity analyses. The CALLY index demonstrated a linear and negative association with all-cause mortality, as well as mortality caused by cancer and cardiac conditions, highlighting its significant prognostic value in patients with oncological conditions.